Theological Philosophy of Encounter: Fostering Interreligious Dialogue in Pluralistic Societies - David Ming; Novita Loma Sahertian (the Faculty of Ushuluddin, UIN Sunan Gunung Djati Bandung, 2025)
This study aims to clarify the role of theological philosophy as a medium for dialogical and interreligious communication in an increasingly pluralistic and globalised world. It seeks to confront epistemological, theological and social barriers that often hinder interfaith dialogue and to propose an inclusive framework grounded in universal ethical values such as love, justice, peace and human dignity. Methodologically, the research adopts a theoretical, descriptive–analytical approach, drawing on key literature in theological philosophy, religious pluralism and interreligious dialogue, with particular attention to the Abrahamic traditions. Through reflective analysis of primary and secondary sources, it identifies major obstacles to interreligious engagement, including divergent epistemological assumptions, historical prejudices, power asymmetries and persistent resistance to pluralism. The findings indicate that a dialogical form of theological philosophy can function as a mediating bridge between religious traditions by emphasising shared ethical commitments without compromising the doctrinal integrity of each faith. Philosophical reflection proves crucial for uncovering common metaphysical and moral ground, for reshaping attitudes to religious “others” and for informing practical strategies, such as dialogical pedagogies, interfaith forums and the constructive use of digital media. The study contributes to current scholarship by integrating theological philosophy more explicitly into both theoretical and practical discussions of interfaith dialogue and by articulating a conceptual framework that links metaphysical reasoning, hermeneutics and social practice. Its implications extend to the promotion of social cohesion in pluralistic societies such as Indonesia, where constitutional pluralism and rich religious diversity coexist with real risks of polarisation.